Acousto-optical nanoscopy of buried photonic nanostructures - Czerniuk, T.; Schneider, C.; Kamp, M.; Höfling, S.; Glavin, B.A.; Yakovlev, D.R.; Akimov, Andrey V.; Bayer, M. (Optical Society of America, 2017)
We develop a nanoscopy method with in-depth resolution for layered photonic devices. Photonics often requires tailored light field distributions for the optical modes used, and an exact knowledge of the geometry of a device is crucial to assess its performance. The presented acousto-optical nanoscopy method is based on the uniqueness of the light field distributions in photonic devices: for a given wavelength, we record the reflectivity modulation during the transit of a picosecond acoustic pulse. The temporal profile obtained can be linked to the internal light field distribution. From this information, a reverse-engineering procedure allows us to reconstruct the light field and the underlying photonic structure very precisely. We apply this method to the slow light mode of an AlAs/GaAs micropillar resonator and show its validity for the tailored experimental conditions.